Altered Nutrition to Onion Plant for Inducing Resistance Against Thrips - Vinutha R K; Hegde M G (Dharwad University of Agricultural Sciences, Dharwad, 2024)
The seasonal incidence of thrips in onion was studied for four consecutive seasons (Kharif 2022, Rabi 2022, Kharif 2023 and Rabi 2023) at Main Agricultural Research Station, University of Agricultural Sciences, Dharwad. The thrips incidence was higher and continuous during rabi and was lower and discontinuous in kharif throughout the study period. The heavy rain fall which washed away the thrips from onion crop surface resulted into significant negative correlation with rainfall and rainy days during kharif season. Thrips were found to thrive well under hot and dry climate resulted in to significant positive correlation with maximum temperature and significant negative correlation with morning and afternoon relative humidity during rabi season. Minimum temperature was found negative and non significant during both kharif and rabi. The onion crop, aged between 60 - 90 days old was found to suffer more by thrips attack in both the seasons. The predators viz, spiders: Oxyopus hindostanicus and Plexippus paykulli, coccinellid: Cheilomenes sexmaculata, predatory thrips: Aeolothrips sp., green lace wing: Chrysoperla sp. and a parasitoid: Ceranisus menes were found to associated with Thrips tabaci Lindeman during the study period. The higher doses of potash, phosphorous and sulphur in combination with recommended dose of nitrogen supported lower number of thrips in onion. Potassium was found to induce resistance against thrips by modifying physiological changes in plant system through increasing total phenols and decreasing total sugar content in onion leaves. Conversely severe infestation of thrips were recorded in plants receiving higher doses of nitrogen in combination with reduced dose of potassium and which appears to make the onion plant susceptible to the thrips attack. The zinc treated plants experienced lower population of thrips among the micronutrient foliar sprays and which was followed by boron and iron. This suggests the need of micronutrients foliar spray as a component in thrips management. The chlorantaniliprole 8.8 SC + thiamethoxam 17.5 SC @ 0.5 ml was most effective against thrips among the premixed insecticides evaluated against thrips on onion. Application of nitrogen, phosphorous, potassium and sulphur at 110:80:120:60 kg per hectare, zinc foliar spray at 45 and 60 days after transplanting and imposition of chlorantaniliprole 8.8 SC + thiamethoxam 17.5 SC @ 0.5 ml whenever thrips population reaches economic threshold level was found superior over recommended practice of fertilizer and insecticide application in thrips management on onion crop. This new strategy of thrips management resulted in to higher B:C ratio of 3.2 due to increased onion bulb yield of 31.5 t/ha which was 28.73 per cent higher than existing recommended practice of onion cultivation.